Variaciones de la concentración de sodio plasmático en el teleósteo eurihalino Jenynsia lineata (Jenyns, 1842) luego del pasaje a soluciones hipertónicas - Gluzman de Pascar, Celia (1968)
The mechanism of secondary or diff ered rngulation of a possib.le hormonal origin in the eurvaline teleost J enysia lineata (Jenyns, 1842) is studied in an attempt to determine if the Cyprinodontiformes constitute a peculiar group of eurvhalines. The results obtained mark an increase -statistically significative- of osmotic pressure and, or the concentration of plasmatic Na in the first hours after the passing of hipertonic solutions and also a gradual decline towards values quite near to those char,acteristic of fresh water. The possible, mechanism that are responsable for the excretion of Na excess are considerate.